A Close Form Solution for the Product Acceptance Determination Based on the Popular Index Cpk. (25th June 2012) - Pearn, W. L.; Wu, C. H.
Abstract : Product acceptance determinations are practical tools for quality control applications involving quality contract on product orders between the vendor and the buyer. It provides the vendor and the buyer rules for product acceptance to meet the preset product quality requirement. As the rapid advancement of manufacturing technology, more than one quality characteristic must be simultaneously considered to improve the product quality because of the product design. In this article, we introduce an efficient product acceptance procedure on the basis of the generalization C pk T index, to deal with lot sentencing problem with very low fraction of defectives. We tabulate the required sample size n and the corresponding critical acceptance value c 0 for various α ‐risk, β ‐risk, and the levels of the lot fraction of defectives that correspond to acceptance and rejecting quality levels. Practitioners can use the proposed method to make reliable decisions in product acceptance. Copyright © 2012 John Wiley & Sons, Ltd.